Scrittura e riscrittura della Vita di San Fermano di Montelupone (BHL 3000-3001) - Licciardello, Pierluigi (Analecta Bollandiana, 2012)
The Vita of St. Firmanus of Montelupone (in the Marches of central Italy), a priest and monk who died in 992, exists in two versions, the first compiled by an anonymous grammaticus (BHL 3000) and the second a revision of it by Thierry of Fleury-Amorbach (BHL 3001). BHL 3000 is published for the first time on the basis of ms. Vallic. tomus XXII; while BHL 3001 is reedited on the basis of the earliest witness (Vat. lat. 7810). The techniques employed in the revision and the alterations in the model of saintlihood between the hypotext and the hypertext are analyzed in the article. In addition two hymns and a mediaeval mass in honour of St. Firmanus are edited.